Fatal police shootings in Sweden - Norée, Annika (Bergen journal of criminal law & criminal justice, 2021)
Something has happened. Over the past six years a total of 17 men have been shot dead by Swedish police. This is a dramatic increase of cases with deadly outcome. Previously, the number of fatal shootings in Sweden had been on average one per year. In total, there have been 44 cases of fatal shootings between 1990-2021., The trend of increasing fatal police shootings is alarming. Prosecutors have generally concluded that the police officers responsible for the shootings fired in self-defense, actual or imagined, to defend themselves or to defend others in dangerous situations. What the police took for a deadly weapon maybe was a harmless dummy. Or the death man – so far it has just been about men – was perhaps unarmed. In the few cases which have resulted in a prosecution, the courts have almost exclusively sided with the defense and concluded that the police officers acted in self-defense. There are few incidents concerning lawful authority, the right of the police to use force to carry out an official duty. , The author analyzes and describes the legal problems connected to the recent dramatic increase of fatal police shootings. She also discusses what may be done within Swedish legislation do to reduce the risk that someone will fall victim to police bullets, and she makes suggestions about improvements to limiting deadly use of force by the police.